The political and social guarantees of the individuals, rights and political freedoms - Saad AL-Arman, Abdu Rahman (Opción, 2019)
The researcher tries to clarify the role of the individuals in protecting their rights and freedoms by electing judicial authority or building up a public opinion.The researcher will follow "Descriptive and Analytical Method" by studying the articles and analyzing them. As a result, citizens in democratic states are considered powerful people due to the power of their parliament. In conclusion, the political parties and civil society organizations hould practice an efficient role to upgrade people’s life and form a better public opinion just like the role usually carried out by the press and social media.